Book Review : A DICTIONARY OF LANGUAGE ACQUISITION: A COMPREHENSIVE OVERVIEW OF KEY TERMS IN FIRST AND SECOND LANGUAGE ACQUISITION - Kaswan Kaswan (STKIP Siliwangi, 2014)
As with language, language acquisition (LA), particularly second language acquisition (SLA) is not simple. SLA is complex and paradoxical. SLA is complex because it cannot be scrutinized using a single approach. SLA is complex; nevertheless it is a curious fact that the study of (SLA has historically been dominated by a single broad approach—that which goes by the name of “cognitive (Atkinson (ed), 2011). Among views on acquisition which can be characterized as cognitive are:1) An infant cannot express concepts in language unless it has previously developed them.2) Both language and cognition are part of a staged maturation program, in which they operate in parallel, supporting each other.3) Innate cognitive tendencies may predispose us:To find patterns in language data (as in data in general).To adopt certain strategies in response to language data.To apply individual learning styles to language data.4) The infant’s limited cognitive capacity renders it more sensitive to the features of language than it might be before or later (Tavakoli, 2012) Apart from cognitivism, the other approaches to SLA are, among others: sociocultural approach, complexity theory, identity approach, language socialization approach, language socialization approaches, conversation analytic approach, and socio cognitive approach (Atkinson (ed), 2011). By examining a variety approaches to SLA , we arrive at the conclusion that SLA is not as simple as we thought. We, therefore, need an authoritative reference to facilitate our better understanding and avoid misconception of SLA. To this end, A Dictionary of Language Acquisition: A Comprehensive Overview of Key Terms in First and Second Language Acquisition by Hossein Tavakoli is incredibly helpful and useful. The function of this book, as stated by the writer, is to collect and synthesize the knowledge base that is already well accepted and that has been well researched. Thus, it is a reference guide which offers an authoritative and encyclopedic survey of key terms and concepts in the areas of language acquisition and development. The volume is intended as a resource to elucidate various concepts, issues, approaches, models, and theories of language acquisition in an efficient and accessible style. To illustrate key terms and concepts in the areas of LA, some of them are quoted and analyzed here. To begin with, first language acquisition, also child language acquisition refers to “the process of learning a native language” (Tavakoli, 2013: 131). Furthermore, Clark (2009) elaborates on this. When children learn a first language, they might construct preexisting notions of what to represent with language and prior notions of communication. Or they could start from nothing and find what is (and isn’t) represented in language. And since languages differ, their acquisition might also be affected by the properties of each language. For example, the type of language could influence the order in which children acquire specific parts of the language and could also make some elements harder or easier to acquire. Their acquisition could also be influenced by social interaction and cognitive development. Factors like these could also determine whether language-learners follow the same path, detect and use the same patterns, and make the same inferences about meanings during acquisition. In sum, first language acquisition (FLA) might be affected by a number of factors, such as the properties of language, social interaction and cognitive development. What do those factors mean? First, language is very complex. It has a sound system that allows us to use a lot of distinct words or vocabulary, and a series of constructions for relating those words. It allows us to express many ideas, describe events, tell stories, recite poems, deliver a speech, and many other activities that make up the societies we live in. In other words, language is an integral part of everyday life that we rely on to convey needs, wants and expectations, thoughts, concerns and plans (Kaswan, 2014). In addition, language is a complex adaptive system, which emerges bottom-up from interactions of multiple agents in speech communities), rather than a static system composed of top-down grammatical rules or principles. The system is adaptive because it changes to fit new circumstances, which are also themselves continually changing (Atkinson (ed), 2011). Another factor affecting FLA might be social interaction. Social-interactionist theory emphasizes the parts played by the child’s environment, its social instincts, its pragmatic needs and its relationship with the car-giver. Those who take this position do not necessarily deny the existence of an innately endowed capacity for language. But they maintain that genetic factors, if they exist, are insufficient on their own to ensure that language develops. Nor is simple exposure to language enough. What is important is the interaction, both linguistic and non-linguistic, which derives from the child’s need to communicate (Tavakoli, 2012: 323). Next factor is cognitive development which refers to “developmental changes in cognitive abilities, processes, and structures” (Tavakoli, 2012: 62). The best known theory of childhood cognitive development is that of Jean Piaget. For Piaget language was both a social and a cognitive phenomenon. It was not an independent modular faculty but part of general cognitive and perceptual processing. Language acquisition was thus dependent upon cognitive development. The child’s level of language was determined by whether it had acquired certain fundamental concepts and by the complexity of the processing operations of which it was capable. Piaget suggested that cognitive development fell into four phases. They constitute a gradual progression in which previous stages are revisited cyclically. The age at which a particular child goes through each stage varies considerably. Each stage has implications for linguistic development. 1) Sensorimotor (birth to 2 years). The child achieves recognition of object permanence (the fact that an object still exists even when it is not in view). This is a prerequisite to the formation of concepts (including lexical concepts). 2) Preoperational (2 to 6 or 7 years). The child’s behavior reflects egocentric thought: it is unable to identify with the views of others. The child’s language progresses through echolalia (repeating others’ utterances) to monologues (speaking aloud what would normally be private thoughts). It may engage in collective monologues with other children, in which participants appear to be taking turns, but express their own ideas without responding to those of others. 3) Concrete operational (6/7 to 11/12). The child’s vocabulary shows signsof organization into hierarchical categories. It develops the concept of con-servation (the recognition that size or quantity is not dependent upon the container) and shows signs of decentration, the ability to consider multiple aspects of a physical problem. It learns to receive and respond to outside ideas. 4) Formal operational (11/12 to adult). The adolescent becomes capable ofabstract reasoning. It learns to construct its own argument structures, can represent hypothetical situations and engages mentally and verbally in problem-solving. Another key concept found in this book is second language acquisition, which refers to the process of learning another language after the native language has been learned. Sometimes the term refers to the learning of a third, fourth, or nth language. The important aspect is that SLA refers to the learning of a non-native language after the learning of the native language. The additional language is called a second language (L2), even though it may actually be the third, fourth, or tenth to be acquired. It is also commonly called a target language (TL), which refers to any language that is the aim or goal of learning. The scope of SLA includes informal L2 learning that takes place in naturalistic contexts, formal L2 learning that takes place in classrooms, and L2 learning that involves a mixture of these settings and circumstances. For example, informal learning happens when a child from Japan is brought to the US and picks up English in the course of playing and attending school with native English-speaking children without any specialized language instruction, or when an adult Guatemalan immigrant in Canada learns English as a result of interacting with native English speakers or with co-workers who speak English as a second language. Formal learning occurs when a high school student in England takes a class in French, when an undergraduate student in Russia takes a course in Arabic, or when an attorney in Colombia takes a night class in English. A combination of formal and informal learning takes place when a student from the USA takes Chinese language classes in Taipei or Beijing while also using Chinese outside of class for social interaction and daily living experiences, or when an adult immigrant from Ethiopia in Israel learns Hebrew both from attending special classes and from interacting with co-workers and other residents in Hebrew. Some might prefer the term second language studies (SLS) as it is a term that refers to anything dealing with using or acquiring a second/foreign language (Tavakoli, 2012: 304-305). As mentioned above, the scope of SLA is informal learning and formal learning. Besides the aforementioned difference, L2 learners appear to tackle the problem of learning a language in similar ways to L1 learners. These similarities are most clearly evident in informal learning situations when learners are attempting to engage in unplanned language use. But there are also differences in the ways in which L2 learners go about cracking the code, and these become most evident in formal learning situations. Informal learning typically takes place in contexts where the input is not consciously structured and the primary focus is on message conveyance, while formal learning occurs in contexts where the input is usually carefully organized and the primary focus is on form. Informal learning involves implicit knowledge, while formal learning is likely to involve at least some explicit knowledge of L2 rules. Formal and informal learning can also be differentiated in the kind of memory learners rely on. Adult L2 learners have access to a more developed memory capacity than L1 learners and when they can use it (or are required to use it, as in many pedagogic learning activities). As touched on above, input is another theme discussed in this book. Input refers to the language to which a listener or reader is exposed; a term used especially in relation to first and second language acquisition. Different kinds of input have been discussed over the years, including comprehensible input (i.e., language that learners can readily understand for its meaning) and modified input (i.e., language that is adjusted so that learners can better comprehend the speaker’s meaning). Some have referred to input as primary linguistic data. The reason for this is that all current theories of acquisition believe that input is the data source for acquisition as opposed to, say, practice, grammar explanations, feedback, and negative evidence. Thus, learners’ developing linguistic systems are a result of input interacting with learners’ internal mechanisms used for processing and storing language. Although all theories of L2 acquisition acknowledge a role for input, they differ greatly in the importance that is attached to it (Tavakoli, 2012: 170-171). Behaviorist theories of L2 acquisition propose a direct relationship between input and output. They emphasize the possibility of shaping L2 acquisition by manipulating the input to provide appropriate stimuli and by ensuring that adequate feedback is always available. Acquisition is thus controlled by external factors, and the learner is viewed as a passive medium. Mentalist theories view input as only a ‘trigger’ that sets off internal language processing. Learners are equipped with innate knowledge of the possible forms that any single language can take, and use the information supplied by the input to arrive at the forms that apply to the L2 they are trying to learn. A common assertion of mentalist theories is that the input is indeterminate, i.e., the information that it supplies is, by itself, insufficient to enable learners to arrive at the rules of the target language. Interactionist theories on input view verbal interaction as being of crucial importance for language learning in a number of ways. Interaction provides learners with input containing the data they need for acquisition. It also affords opportunities to experiment through production and to receive feedback on these attempts, thereby making the ‘facts’ of the L2 salient. However, it is argued that an interactionist model is agnostic as to whether input determines acquisition or feeds the learner’s innate language acquisition device. The final theory offers a very different view of the relationship between input and learning. Sociocultural theory does not distinguish between input and output but rather views language acquisition as an inherently social practice that takes place within interaction as learners are assisted to produce linguistic forms and functions that they are unable to perform by themselves. Subsequently, internalization takes place as learners subsequently move from assisted to independent control over a feature. Bilingualism is common almost around the world, where at least two languages are spoken. Language acquisition cannot be divorced from bilingualism in that FLA and SLA occur simultaneously. Therefore, the effect of one language on the learning of another is inevitable. This phenomenon is termed as transfer, which is also highlighted in this book. Two types of language transfer may occur. Positive transfer is transfer which makes learning easier, and may occur when both the native language and the target language have the same form. For example, both French and English have the word table, which can have the same meaning in both languages. Negative transfer is the use of a native-language pattern or rule which leads to an error or inappropriate form in the target language. Negative transfer can be referred to as interference, in that previously learned material interferes with subsequent material—a previous item is incorrectly transferred or incorrectly associated with an item to be learned. For example, a French learner of English may produce the incorrect sentence I am here since Monday instead of I have been here since Monday, because of the transfer of the French pattern Je suis ici depuis lundi (‘I am here since Monday’). The term transfer is closely associated with behavioristic theories of L2 learning. According to behaviorist theories of language learning, the main impediment to learning was interference from prior knowledge. In effect, the behaviorist accounts of transfer, as reflected in the contrastive analysis hypothesis in particular, overpredict both the transferability of specific items (i.e., they fail to explain when they are transferred and when they are not), and transfer load (how much is transferred). However, it is now widely accepted that the influence of the learner’s native language cannot be adequately accounted for in terms of habit formation. Transfer is not simply a matter of interference or of falling back on the native language. Nor is it just a question of the influence of the learner’s native language, as other, previously acquired second language can also have an effect. This suggests that the term L1 transfer is inadequate. It is argued that a superordinate term that is theory-neutral is needed. Increasingly, researchers have thought to identify the conditions that promote and inhibit transfer, (i.e., constraints on transfer). It is argued that constraints can involve general cognitive capacities including ‘perception and memory’ and ‘principles of language either totally or partially independent of other human capacities’, i.e., they can be cognitive or linguistic. A number of constraints have been identified: (1) social factors (the effect of the addressee and of different learning contexts on transfer), (2) markedness (the extent to which specific linguistic features are special in some way, (3) prototypicality (the extent to which a specific meaning of a word is considered core or basic in relation to other meanings of the same word, (4) language distance and psychotypology (the perceptions that speakers have regarding the similarity and difference between languages), and (5) developmental factors (constraints relating to the natural processes of interlanguage development). Nonstructural factors such as the nature of the tasks a learner is performing and individual learner differences (e.g., personality and age) also constrain L1 transfer. Some of these factors are clearly external in nature, for example social factors, whereas others are equally clearly internal, for example developmental factors. Other constraints, however, have both an external and internal dimension—for example, markedness and language distance/ psychotypology. (Tavakoli, 2012: 347-349). In addition to the key concepts and themes exposed above, the book highlights many other ones which are very typical of language acquisition , such as interlanguage, affective filter hypothesis, error analysis, computational model of SLA, and so forth. Being basic and superficial, the dictionary might be a tremendous help to guide novice readers who intend to explore language acquisition.